Sistem Pembayaran E-Commerce di Indonesia dalam Perspektif Islam - Septia Arum Ningsih; Eka Nurfadhilah (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This study contains an analysis of the e-commerce payment system in Indonesia from an Islamic perspective as well as the methods of e-commerce payments and the sharia principles that underlie the payment system. The approach taken is a qualitative approach with a literature review from academic publications and relevant sources. The results of this study show that the e-commerce payment system in Indonesia, if it is in accordance with the Islamic perspective, must be based on sharia principles and Islamic law. The Islamic financial system itself is sourced from the Qur'an and the Sunnah, as well as from the interpretation of scholars of these sources of revelation. Payment instruments in Islamic principles include cash, hawala (money transfer), wakalah bil ujrah, sharia payment cards, checks and bilyet, and electronic money. The Islamic payment system has its own opportunities and challenges, especially in terms of technological innovation, transaction security, and compliance with sharia principles. This research is expected to be an academic and practical reference to understand the implementation of the e-commerce payment system in Indonesia that is in accordance with Islamic values and supports the sharia-based digital economy.